MetalMUMPs resonator for acetone vapor sensing - Rabih, A.A.S. (Institute of Electrical and Electronics Engineers Inc., 2017)
Acetone vapor monitoring is essential in workplace for human health and safety, where exposure to acetone concentration more than 176 parts per million (ppm) can cause damage to eyes, liver, kidneys and central nervous system. In addition, acetone in exhaled breath is known to be good biomarker for non-invasive screening of diabetes. The most common used acetone vapor sensors are based on metal oxide semiconductor sensors, which work at higher temperatures, and hence consume more power. This paper reports MetalMUMPs device for acetone vapor sensing for environmental monitoring. The device is based on electrothermal actuation and capacitive sensing using differential capacitance measurement technique. MS3110 universal capacitive readout circuit was used to readout the small change of the static capacitance when the device is actuated using 0.71 Vrms with a driving frequency range of 0.5 kHz-8 kHz. The output signal of the circuit is given as a voltage and it can be directly related to the capacitance change. The output voltage change was found to increase linearly with increasing the acetone vapor concentration from 100 ppm to 500 ppm with a concentration sensitivity of 0.65 mV/ppm. © 2017 IEEE.